Quality‐of‐service‐aware fair bandwidth allocation scheme for fibre wireless networks. Issue 3 (1st May 2016) - Sarigiannidis, Antonios; Nicopolitidis, Petros
Abstract : Fibre wireless (FiWi) access networks constitute a promising candidate to meet the demanding challenges of the modern bandwidth‐hungry services and applications. Due to the dynamic nature of the network traffic in access domains, the bandwidth allocation process has to provide a fair and effective coordination between the users including an efficient quality‐of‐service (QoS) plan. However, the majority of the bandwidth allocation schemes neglect the measured QoS parameters, such as latency, jitter, and packet loss. In addition, the fairness issue is not always taken into account. As a result, the packet delivery of sensitive data streams is often problematic and the QoS guarantees are not addressed or even totally ignored. In this study, the authors present a novel bandwidth allocation policy which applies an efficient weighted‐based, QoS‐aware schedule in modern FiWi networks with fairness support. The innovation behind the proposed scheme lies in the direct association of the measured QoS parameters with the applied fair bandwidth allocation process.